INTRAPELVIC PRESSURE CHANGES IN UNILATERAL OBSTRUCTIVE NEPHROPATHY - Shah, Attaullah; Khan, F. A; Saleem, Saleem (Journal of Ayub Medical College Abbottabad, 2000)
Background: Ureteric obstruction leads to increase in the Intrapelvic pressure and this ultimately affects the kidney leading to structural and functional changes. It is not possible to study it in human beings. Numerous animal models have been employed in the past. We studied these changes by using dog as the experimental model. Methods: Intrapelvic pressure changes were studied in dogs. Right side ureters were exposed by a midline incision and were cannulated with feeding tubes. Feeding tubes were connected to sphygmomanometer and any type of leakage was excluded. The intrapelvic pressure was raised to 150 mmHg for 30 minutes. X-ray films were taken to reveal the escape routes in the kidney. Results: It was observed that the intrapelvic pressure did not remain as such and a drop of pressure by 10-12 mmHg was noted in 30 minutes. The kidney parenchyma was outlined with streaks of dye extending from the pelvis into the renal tissue. This showed pyelovcnous, pyelolymphatic or pyelotublar pathways which arc normally lying dormant.